Axiological Analysis of Knowledge Cultivation and Its Contemporary Contextualization (Study of Umar Bin Khattab's Thought) - Hafizh, Muhammad; Lailah, Soimah; Astuti, Widia; Cholid, Nur (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The axiological known today in the educational sector in principle has been applied by Umar bin Khattab. As a caliph who was more concerned with managing the political stability of his period, of course, linking him to educational theory was rather difficult. Therefore, the purpose of this study is to reveal Umar bin Khattab's ideas about the benefits and value of the spread of knowledge through the axiological approach of philoSophy. The method used is literature-based qualitative (data Sources are literature related to the thoughts of Umar bin Khattab) and analyzed descriptively. The results of his research are axiological values in the thought of Umar bin Khattab in the form of 1) religious value: the creation of peace of mind, morals to educators, and becoming capital in worship, 2) the value of truth and goodness: knowledge can consider one's behaviour and work is right and good Sothat it can get sustenance for him and benefit others, 3) Social value: a gainer of knowledge must provide benefits to Society and must not harm it in the slightest, and 4) Islamic economic value: the acquisition of material from the acquisition of knowledge with halal and good. Contextualizing the four values in the modern era with the habituation method, learning Social science materials perfectly, and managing the state budget for education funds properly.